2015
DOI: 10.2147/tcrm.s87595
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of antibiotic and analgesic use in the Oral Surgery Department of the University Dentistry Clinical Center of Kosovo

Abstract: BackgroundBecause Kosovo has no reliable information on antimicrobial and analgesic use in dental practice, the survey reported here evaluated the antibiotic and analgesic prescriptions in the Oral Surgery Department of the University Dentistry Clinical Center of Kosovo (UDCCK).MethodsThe data of 2,442 registered patients for a 1-year period were screened and analyzed concerning antibiotic and analgesic use as per standards of rational prescription.ResultsDentistry doctors prescribed antibiotics significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…2,3 Nonsteroidal anti-inflammatory drugs (NSAID), opioids, and analgesics are frequently prescribed by dental practitioners. 3,4,5 Research shows an overall increase in the prescription of medicines to control pain. 6,7,8 It is recognized that millions of people suffer from untreated pain around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Nonsteroidal anti-inflammatory drugs (NSAID), opioids, and analgesics are frequently prescribed by dental practitioners. 3,4,5 Research shows an overall increase in the prescription of medicines to control pain. 6,7,8 It is recognized that millions of people suffer from untreated pain around the world.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, the majority and most recent populational research on analgesics prescriptions by dental practitioners does not evaluate the influence of social health determinants. [5][6][7][8] In this study, we aimed to describe dental prescriptions of NSAID, opioids, and analgesics dispensed by the Brazilian National Health System (BNHS, SUS in Portuguese) of a Southeastern state and to analyze their association with socioeconomic and oral health care services' characteristics at municipal-level from January to December 2017.…”
Section: Introductionmentioning
confidence: 99%
“…These data show an improvement in the antibiotic of first choice compared with previous studies in Kosovo, where the antibiotic of first choice was co-amoxiclav, regardless of the institutions where the studies were conducted. [11][12][13] This improvement in prescribing patterns at HUSCK could be due to the fact that dentists working in a university/hospital setting are more confident in their treatment decisions and adhere to guidelines. 14 The most recent survey conducted in Kosovo based on official data of patients from secondary and tertiary health care facilities showed that antibiotic use varied according to the county/city surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Generic drug prescriptions in the present study were lower than the WHO standard value (100%), and slightly more than onethird of the branded drugs were prescribed to the patients, which is lower than the branded drug prescriptions reported by Fader and his coinvestigator from their study conducted in Nigeria 4 . Similarly, studies conducted in India, Nepal, and Kosovo highlighted low generic and high branded drug prescription among the patients visited to the dental clinic 6,25,26 . Moreover, percentage of encounters with an antibiotic prescription (32.02%) was higher than the WHO standard value (20-27%) and mostly drugs were prescribed from essential drug list of the country 6,26 .…”
Section: Drug Prescribing Pattern As Per Who Prescribing Indicatorsmentioning
confidence: 92%
“…Similarly, studies conducted in India, Nepal, and Kosovo highlighted low generic and high branded drug prescription among the patients visited to the dental clinic 6,25,26 . Moreover, percentage of encounters with an antibiotic prescription (32.02%) was higher than the WHO standard value (20-27%) and mostly drugs were prescribed from essential drug list of the country 6,26 . However, a study conducted in Nepal described a smaller number of drugs prescribed from EDL 25 .…”
Section: Drug Prescribing Pattern As Per Who Prescribing Indicatorsmentioning
confidence: 92%